PENGARUH PENAMBAHAN PATI DAN PLASTICIZER GLISEROL TERHADAP SIFAT MEKANIK PLASTIK BIODEGRADABLE - Sitti Nurrahmi; Sity Nuraisyah; Hernawati Hernawati (Universitas Islam Negeri Alauddin Makassar, 2020)
Biodegradable plastics are plastics that will decompose in nature with the help of microorganisms. The use various of starch as the main material of plastic manufacturing has great potential because in Indonesia there are different starch crops. To obtain bioplastics, starch is added to the plasticizer glycerol, in order to obtain a more flexible plastic and elastic. This study reviews the use of starch to obtain good mechanical properties of biodegradable plastics. Addition various of starch affecting the mechanical properties of biodegradable plastics. But, addition of plasticizer glycerol on many kinds of starch lower the value of tensile strength and raising the value of elongation. But, when added chitosan and glycerol, increasing the value of tensile strength and lower the value of elongation.